ANALISIS KINERJA KEUANGAN PADA PT. SURYA TOTO INDONESIA Tbk - iwin arnova (Jurnal Ilmu Akuntansi, 2020)
Analysis of financial performance at Pt. Surya Toto Indonesia Tbk. Financial ratio analysis is intended to assess the risks and opportunities in the future. Measurement and relationship of one item to another item in the financial statements that appear in financial ratios can provide meaningful conclusions in determining the level of financial health of a company. This study aims to assess the financial performance of PT. Surya Toto Indonesia Tbk. in 2016-2018. The analysis was carried out using various financial ratios namely profitability ratios, liquidity ratios, solvency ratios and activity ratios to see the company's performance during 2016 to 2018. Rate of return on net sales, Return on Equity of PT. Surya Toto Indonesia Tbk financial performance is not good. The value of Return On Assets, Current Ratio in 3 consecutive years is 2 times, which means the company's profitability is good. in 2018 is 2 times, and PT. Surya Toto Total debt to total assets, Interest coverage ratio, Receivables turnover ratio, Inventory turnover ratio, Accounts payable turnover where financial performance is good.